USING INNOVATIVE METHODS IN TEACHING SPEAKING SKILLS - Hasan Uzairovich Akhmedov (European Science Publishing, 2024)
Currently, modern methods of teaching are widely used in the educational process. The use of modern teaching methods can lead to greater effectiveness in teaching. It is advisable to choose these techniques based on the didactic function of each lesson. Enriching the traditional form of teaching with a variety of methods that enhance the learner's performance will lead to an increase in the level of self-learning. This article deals with these problems and, moreover, further examples are provided.
Keywords: Education, learning process, teaching methods, learning process, didactic literature.